I would like to ask for your help to derive some expressions. Let the labor demand curve be described by:

$N^D = N^D(W/P, \bar{K}), \quad N^D_{W/P}= \frac{1}{F_{NN}}< 0, \quad N^D_K = -\frac{F_{NK}}{F_{NN}} > 0$

and the labor supply curve by:

$W/P^e = g(N^S)$

My question is, how can I express these two curves in terms of elasticities? I know that the result should be:

$\frac{dN^D}{N^D} = \frac{d\bar{K}}{\bar{K}} - \varepsilon_D \Big(\frac{dW}{W}-\frac{dP}{P} \Big) \\ \frac{dN^S}{N^S} = \varepsilon_s \Big( \frac{dW}{W}-\frac{dP^e}{P^e}\Big)$

where $\varepsilon_D=-F_{NN}/(NF_{NN})$ and $\varepsilon_S = g(N)/(Ng_N)$ denote the wage elasticities of labor demand and labor supply, respectively.

Thank you for your help and time.

  • 1
    $\begingroup$ can you please first show us your attempt per our rules on self study questions? (for more on the rules see our help center) $\endgroup$
    – 1muflon1
    Jan 16 '21 at 10:38

This result is presented on page 14 of Foundations of Modern Macroeconomics. The key is to total differentiate both expressions.

Start with the supply of labor:

\begin{gather} W/P^e = g(N^S) \\ d(W/P^e) = d\Big( g(N^S) \Big) \\ \frac{1}{P^e} dW - \frac{W}{(P^e)^2}dP^e = g_NdN^S \\ dN^S = \frac{1}{g_N}\frac{dW}{P^e} - \frac{1}{g_N}\frac{W}{P^e}\frac{dP^e}{P^e} \\ dN^S = \frac{1}{g_N}\frac{dW}{P^e} - \frac{g(N^S)}{g_N}\frac{dP^e}{P^e}, \quad \text{where} \quad W/P^e = g(N^S) \\ dN^S = \frac{1}{g_N}\frac{g(N^S)}{W}dW - \frac{g(N^S)}{g_N}\frac{dP^e}{P^e} \\ dN^S = \frac{g(N^S)}{g_N} \bigg[ \frac{dW}{W} - \frac{dP^e}{P^e} \bigg] \\ \frac{dN^S}{N^S} = \frac{g(N^S)}{N^Sg_N} \bigg[ \frac{dW}{W} - \frac{dP^e}{P^e} \bigg] \end{gather}

To derive the expression for the demand of labor, one can follow a similar process (I will ommit the superscript $N^D$ for simplicity, but we know we are talking about labor demand). Recall that the FOC of the firm's problem is given by:

\begin{gather} PF_N(N,\bar{K}) = W \\ F_N(N,\bar{K}) = \frac{W}{P} \\ d\Big( F_N(N,\bar{K}) \Big) = d\Big( W/P \Big) \\ F_{NN}dN + F_{NK}d\bar{K} = \frac{1}{P}dW - \frac{W}{P^2}dP \\ F_{NN}dN + F_{NK}d\bar{K} = F_N\frac{dW}{W} - F_N\frac{dP}{P} \\ F_{NN}dN = F_N \bigg[ \frac{dW}{W} - \frac{dP}{P} \bigg] - F_{NK}d\bar{K} \\ dN = -\frac{F_{NK}}{F_{NN}}d\bar{K} + \frac{F_N}{F_{NN}}\bigg[ \frac{dW}{W} - \frac{dP}{P} \bigg] \\ \frac{dN^D}{N^D} = -\frac{F_{NK}}{N^DF_{NN}}d\bar{K} + \frac{F_N}{N^DF_{NN}}\bigg[ \frac{dW}{W} - \frac{dP}{P} \bigg] \\ \frac{dN^D}{N^D} = \frac{d\bar{K}}{\bar{K}} + \frac{F_N}{N^DF_{NN}}\bigg[ \frac{dW}{W} - \frac{dP}{P} \bigg], \quad \text{where} \quad KF_{NK} = -NF_{NN} \end{gather}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.